The role of Clec11a in bone construction and remodeling - Xu, Ke; Huang, Rui-qi; Wen, Ruiming; Yang, Yao; Cheng, Yang; Chang, Bo (Frontiers in Endocrinology, 2024)
Bone is a dynamically active tissue whose health status is closely related to its construction and remodeling, and imbalances in bone homeostasis lead to a wide range of bone diseases. The sulfated glycoprotein C-type lectin structural domain family 11 member A (Clec11a) is a key factor in bone mass regulation that significantly promotes the osteogenic differentiation of bone marrow mesenchymal stem cells and osteoblasts and stimulates chondrocyte proliferation, thereby promoting longitudinal bone growth. More importantly, Clec11a has high therapeutic potential for treating various bone diseases and can enhance the therapeutic effects of the parathyroid hormone against osteoporosis. Clec11a is also involved in the stress/adaptive response of bone to exercise via mechanical stimulation of the cation channel Pieoz1. Clec11a plays an important role in promoting bone health and preventing bone disease and may represent a new target and novel drug for bone disease treatment. Therefore, this review aims to explore the role and possible mechanisms of Clec11a in the skeletal system, evaluate its value as a potential therapeutic target against bone diseases, and provide new ideas and strategies for basic research on Clec11a and preventing and treating bone disease.